Moderating role of self-congruence: Impact of brand personality on Brand attachment through the Mediating role of Trust - Amjad, Asma; Amjad, Fiza; Jamil, Khalid; Yousaf, Sharjeel (Information Management and Business Review, 2018)
Increasingly companies are focused on searching for ways to create strong brand connections with consumers. It is illustrated that such connections lead to higher levels of consumer loyalty, which increases companies’ financial performance. The main purpose of this study is to explore the impact of brand personality on brand attachment through the mediating role of trust. Also investigate the moderating role of self-congruence on the relationship between brand personality and brand trust. SPSS 23 is used to analyze the data. Data was collected through survey questionnaire technique and snow-ball sampling technique was used for data collection. Analysis reveal Brand personality have significant and positive relationship with brand trust. On the other side trust significantly enhance the brand attachment. While the results prove that self-congruence have significant moderating effect on the relationship between brand personality and brand trust.